Association Between Diabetes Mellitus and Hypertension Severity at a Primary Health Care Center in Indonesia: A Cross-Sectional Study - Asdar Amin; Yuni Asri; Ananda Sagita Maharani (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Background: Hypertension remains a major public health problem, particularly in primary health care settings. The coexistence of diabetes mellitus may contribute to increased hypertension severity; however, evidence from primary care data in Indonesia remains limited. Objective: This study aimed to examine the association between diabetes mellitus and hypertension severity among patients attending a primary health care center in Indonesia. Methods: A cross-sectional study was conducted using secondary data obtained from medical records at a primary health care center in 2025. A total of 84 patients with hypertension were included using total sampling. Hypertension severity was classified into stage 1 and stage 2. Bivariate analysis was performed using the Chi-square test or Fisher’s exact test as appropriate, with statistical significance set at p < 0.05. Data were analyzed using SPSS version 26. Results: Of the 84 participants, 33.3% had diabetes mellitus. Stage 2 hypertension was more prevalent than stage 1 hypertension. Diabetes mellitus was significantly associated with hypertension severity (p = 0.029), with a higher proportion of patients with diabetes mellitus presenting with stage 2 hypertension. Conclusion: Diabetes mellitus was significantly associated with greater hypertension severity in a primary health care setting. These findings highlight the importance of integrated management.